Controlling solubility: a chemical approach toward preparing nitrogen-doped hollow carbon nanospheres. Issue 3 (23rd December 2019) - Lin, Hua; Ye, Wanyue; Liu, Yingcen; Liu, Minghui; Song, Caicheng; Zhang, Hao; Lu, Rongwen; Zhang, Shufen
Abstract : A new protocol to synthesize nitrogen-doped hollow carbon nanospheres by controlled compositional distribution of polymeric component, followed by post-treating of formaldehyde solution. Abstract : Nitrogen-doped hollow carbon nanospheres have attracted considerable attention in various fields such as catalysis, biomedicine, adsorption and energy storage/conversion. The most widely used methods used to prepare these materials are template-based routes, however, the operating procedures are tedious and the mechanism of their formation is still unclear. Here, we have designed a new protocol to synthesize nitrogen-doped hollow carbon nanospheres by preparing and post-treating nanospheres with area-specific distribution, guided by solubility control throughout the entire synthetic process. The hollow inner structure was formed based on the reversibility of chemical reactions without any template assistance. The forming mechanisms of novel solid polymer spheres and the hollow structure have been investigated. The size, morphology and shell thickness of the spheres could be tuned by changing the amount of reactants, the ratio of acetone/water and a subsequent treatment process. Furthermore, the nitrogen-doped hollow carbon nanospheres exhibited both high stability and capacity as a Li–S battery cathode with a capacity of 528 mA h g −1 after 300 cycles at 0.5C.